Analisis Kinerja Keuangan Perkebunan terhadap Standar SOP di PT. Perkebunan Nusantara III Kebun Bandar Selamat - Cici Putri Ardyanti; Arnida Wahyuni (Universitas Muhammadiyah Surabaya, 2023)
The research will discuss the Analysis of Plantation Financial Performance Against SOP Standards at PT. Perkebunan Nusantara III Kebun Bandar Selamat. This research was conducted using qualitative methods. As part of this investigation, operational activities and identification results were analyzed. This study was conducted through interviews, observations and document analysis to analyze the financial performance of the plantations based on the SOP standards of PT Perkebunan Nusantara III Kebun Bandar Selamat. This study shows the results or results achieved by the company's management in effectively performing the company's asset management functions within a certain period of time. In this way, the company can improve its financial performance better than the operating standards, so the company can also evaluate each improvement and provide the correct response measures, and provide guidance for formulating financial performance based on the evaluation of financial performance. The right decisions of a company can determine its sustainability.